Rectal Prolapse in a Ring-Tailed Coati (Nasua nasua): RELATO DE CASO - Rech Cassanego, Guilherme; Canevese Rahal, Sheila; Corrêa de Camargo , Gabriel; Duarte da Costa, Leonardo; Marchionatti Pigatto, Anita; Yuji Tokashiki , Erick; Carrera Pinhatti , Carime; Tonetti Claro , Ana Julia (Acta Scientiae Veterinariae, 2024)
Background: Coatis are mammals of the order Carnivora, Procyonidae family. Despite the animals being widely distributed in Brazil, the species is classified as threatened in the Rio Grande do Sul state. The main threat factor for the species is deforestation and fragmentation of forests, as well as hunting and being run over on highways. Captivity coatis are subject to nutritional disorders, with adipose tissue accumulation in the abdominal region and obesity. In addition, procionids can present ectoparasites, such as fleas, lice, and ticks. Since there is a lack of information regarding diseases in captivity animals, this report aimed to describe a case of rectal prolapse in a coati. Case: An approximately 2-year-old captivity ring-tailed coati (Nasua nasua) male, 1.7 kg of body mass, was restless and uncomfortable when sitting down after fighting with other animals in the group. Physical examination revealed a 5 cm prolapse, initially managed by manual reduction and purse-string suture around the anus. The copro-parasitological exams using the Willis-Mollay and Faust techniques were negative. Complete blood count showed mild normochromic normocytic anemia, hypoproteinemia, thrombocytopenia, and leukocytosis due to neutrophilia and monocytosis. Biochemical examination revealed hypocalcemia, and the animal was treated with calcium. Rectal prolapse recurred even after the purse-string suture. Therefore, incisional colopexy was performed through a ventral midline celiotomy to promote a permanent adhesion between the colon and abdominal wall. The animal evolved uneventfully and returned to its original enclosure 30 days after surgery. However, the coati was kept separate from the others until complete readaptation. In the last evaluation 6 months after colopexy, the animal showed no signs of recurrence and had a total integration into the group. Discussion: Several factors may contribute to the development of complete rectal prolapse in domestic dogs and cats, such as prostatic diseases, cystitis, urolithiasis, constipation, rectal foreign bodies, and perineal surgeries. However, these factors have not been identified in the current case. Furthermore, the lesion may occur secondary to colitis, enteritis, or endoparasitism in young domestic dogs and cats. In the present case, the animal was an adult whose coproparasitological examination was negative, eliminating these causes. On the other hand, 2 factors may have contributed, including the fight with other individuals of the same species and hypocalcemia. Although these 2 factors resolved with the separation of the animal and calcium replacement treatment, the prolapse recurred even after the purse-string suture. It is also worth mentioning that the animal had no clinical signs related to hypocalcemia, which is associated with several diseases in domestic dogs and cats, including traumatic processes. Colopexy was the 2nd treatment option in the current case. The technique promotes a permanent adhesion between the colon and abdominal wall, thus preventing caudal movement of the colon and rectum. Colopexy has been used in domestic dogs and cats with recurrent rectal prolapse without the identification of predisposing factors, which include the present case. In conclusion, the present case showed a good evolution of the incisional colopexy technique in the recurrence of rectal prolapse in the ring-tailed coati, whose underlying cause could not be established. To the best of the authors’ knowledge, this is the 1st report of the condition in coatis. Keywords: colon, colopexy, surgery, wildlife. Título: Prolapso retal em quati-de-cauda-anelada (Nasua nasua) Descritores: cólon, colopexia, cirurgia, animais selvagens.